History on the role of hormones and contraceptives in lupus (2011)
In this paper we present the diverse events leading up to know in depth the relationship between hormones and lupus, and the authors who participated in this research. We reviewed published articles on the subject since the early twentieth century. We especially count on the birth control pill, how it was discovered and how this interacts with lupus, as well as other hormones. Finally we review the major research being conducted between hormones and lupus © 2011 Asociación Colombiana de Reumatología